In and Off the Show: Co-constructing ‘invisibility’ in an Interpreter-Mediated Talk Show Interview - Wadensjö, Cecilia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis paper examines how participants in an interpreter-mediated televised interview communicate involvement in a shared event. It takes as a case in point an interview where Michail Gorbachev, accompanied by his interpreter Pavel Palazchenko, appear on the ALL TALK show, hosted by the BBC journalist Clive Anderson. Detailed analysis of the interview demonstrates how the interpreter’s physical presence helps shape a shared image of him as someone “just translating.” It is suggested, that the efficiency by which his translation work is communicated, apart from owing to the interpreter’s fluency in English and Russian, is due to the others’ communicative behaviour. While addressing one another as conversational partners and interacting with the studio audience and the viewer, they cast him variably as sharing and not fully sharing their ongoing exchange. Moreover, his efficiency as interpreter is shown to be a result of his ability to anticipate grammatical and pragmatic features of turn composition. Overall, the study demonstrates how detailed analyses of real-life interpreter-mediated interaction can assist in explaining and teasing apart the illusive “invisibility” of interpreters.